Application of First Law of Thermodynamics in Merpati Putih Martial Art Practice to Develop Human’s Inner Energy - Sudiro, Pratondo Ario Seno; Rizzy, Al-Fadel Arman (MUNISI: Military Mathematics and Natural Sciences, 2025)
Merpati Putih is one of Indonesian traditional martial art that had been practiced since the New Mataram Kingdom but still being exist at the present. It activates inner energy based on calmness. Inner energy is a living energy from human’s cell that can be developed by anaerobic-hypoxic or breathing practice regularly. This research aims to discuss about application of First Law of Thermodynamics in Merpati Putih regular practice empirically. The applied method was based on the researchers’ own experiences as member of Merpati Putih’s practice group (Kelompok Latihan/Kolat) combined with descriptive qualitative method by observing existing researches and also mathematic calculations use First Law of Thermodynamics formulas to identify value of potential energy that can be developed by Merpati Putih regular practice. Result of the research is 50 kilograms human who practice regularly would have potential energy that can break 238 aerated concrete blocks (Hebel).